Hydrotherapy: An innovative treatment for obese Malaysians - Noordin, M. Hazim M.; Ahmad, Hartini; Baharin, Shamsuddin (2015)
Malaysia is ranked as a country with the most obese population in the Southeast Asia region, and placed sixth in the Asia Pacific. Obesity does not only influence the persons’ mobility and quality of health, but could also link to medical leaves and absenteeism affecting the overall workforce productivity and efficiency.Routine physical activity is essential for good health and it is particularly important for those who are trying to lose weight or to maintain a healthy weight.However, it is disheartening to note that only 32.6 percent Malaysians above the age of 15 are involved in physical exercise or vigorous sports.There is an emergence of many types of hydrotherapy system, which are either active or passive and these can be at hospital settings, public places or in individual homes. Such hydrotherapy, if properly programmed can promote the physical activity amongst the obese in Malaysia. Current research on the use of active and passive hydrotherapy for obesity treatment was carried out.Subjects of both sexes and diverse age ranges, immersed themselves in a heated pool within hospital setting and in a bath tubs with high energy turbulent movement of medium temperature water. These hydrotherapy sessions provide a form of physical exercise in water as compared to on the land exercise.The findings of the hydrotherapy sessions have shown encouraging results.Quantitative data was analysed, with the help of descriptive statistics and paired sample t-test.Qualitative data was analysed manually with help of thematic analysis and specialized qualitative assessment software.This study reveals that hydrotherapy has improved patient’s mobility, flexibility and exercise capability.Results reveal the reduction in the weight of subjects, with both quantitative and qualitative data results show that Hydrotherapy improved the quality of life in term of body pain reduction and general health improvement.Therefore, it can be concluded that the hydrotherapy can be seen as extensions of exercise and one of the methods in reducing body fat and weight.